Regionalization vs. Globalization - Hideaki Hirata; M. Ayhan Kose; Christopher Otrok (Koç University-TÜSİAD Economic Research Forum (ERF), 2013)
Both global and regional economic linkages have strengthened substantially over the past quarter century. We employ a dynamic factor model to analyze the implications of these linkages for the evolution of global and regional business cycles. Our model allows us to assess the roles played by the global, regional, and country-specific factors in explaining business cycles in a large sample of countries and regions over the period 1960-2010. We find that, since the mid-1980s, the importance of regional factors has increased markedly in explaining business cycles especially in regions that experienced a sharp growth in intra-regional trade and financial flows. By contrast, the relative importance of the global factor has declined over the same period. In short, the recent era of globalization has witnessed the emergence of regional business cycles.
Keywords: C11; C32; E32; F41; F42; 330; business cycles; comovement; synchronization; trade linkages; financial linkages; Konjunktur; Regionale Konjunktur; Internationale Wirtschaftsbeziehungen; Konjunkturzusammenhang; Welt